Evaluating the potential of natural reproduction and artificial techniques to increase Acropora cervicornis populations at Discovery Bay, Jamaica - Quinn, Norman J.; Kojis, Barbara L. (Revista de Biología Tropical, 2006)
Shallow water Acropora species have become uncommon on north coast Jamaican coral reefs owing to a number of factors. On many reefs, algae have taken their place. The result is loss of habitat for many species of fish and invertebrates and less attractive reefs with fewer fish. These reefs appear to be prime candidates for coral restoration. However, the potential for coral to naturally recover should be examined before efforts to restore reefs are undertaken. Reef restoration is unnecessary if the population has the capacity to recovery through natural means. We observed that the rate of settlement of Acropora spat in the Caribbean is much lower than the spat settlement rate of several other Caribbean coral families and much lower than Acropora spat settlement rates in the South Pacific. A very low percentage of apparently healthy colonies of A. cervicornis possessed developing gametes in July 2005, a month before spawning. It appears that the long-term survival of remnant A. cervicornis populations is threatened unless successful sexual reproduction is restored. Several techniques were used to test transplant methods for restoring A. cervicornis populations. The mean survivorship and growth rate of one technique was >75% and nearly 250% per annum, respectively. Working with hotel operators, environmental groups, and local fishers, we are attempting to reintroduce A. cervicornis to sites where it previously existed and increase coral biomass and complexity at these sites. Reefs with greater A. cervicornis biomass have larger edible fish populations. With localized protection of these restored reefs we anticipate an increase of larger edible fish not only on reefs within the restored protected areas but also on adjacent reefs. Furthermore, increased coral and fish biodiversity improves the attractiveness of the reef community for divers and snorkelers. Rev. Biol. Trop. 54 (Suppl. 3): 105-116. Epub 2007 Jan. 15.